2021
DOI: 10.1159/000512177
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Living Donor Kidney Transplantation: The Role of Donor’s Kidney Function

Abstract: <b><i>Introduction:</i></b> Living donor kidney transplant (LDKT) is one of the best therapeutic options for end-stage kidney disease (ESKD). Guidelines identify different estimated glomerular filtration rate (eGFR) thresholds to determine the eligibility of donors. The aim of our study was to evaluate whether pretransplant donor eGFR was associated with kidney function in the recipient. <b><i>Methods:</i></b> We retrospectively studied LDKT recipients who receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Similarly, in a French study involving 90 donor-recipient pairs, donor age and eGFR were the strongest predictors of recipient kidney function at three years on multivariate analysis [13].…”
Section: First Authormentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, in a French study involving 90 donor-recipient pairs, donor age and eGFR were the strongest predictors of recipient kidney function at three years on multivariate analysis [13].…”
Section: First Authormentioning
confidence: 81%
“…In a retrospective study involving 206 living donor renal transplants, Hawley et al reported that pre-transplant donor eGFR was the most significant predictor of six-month recipient graft function [ 12 ]. Similarly, in a French study involving 90 donor-recipient pairs, donor age and eGFR were the strongest predictors of recipient kidney function at three years on multivariate analysis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decision making is complex, as it involves HLA matching, vascular anatomy, CMV status etc., but donor kidney function is an important consideration in terms of ensuring the best recipient outcomes. 30,31…”
Section: Importance Of Gfr Assessment For Donor Candidatementioning
confidence: 99%
“…In addition to donor safety, donor candidate GFR assessment is relevant when transplant candidates have the option of multiple donor candidates, as is often the case in kidney paired donation, or when multiple friends and family members offer to donate. The decision making is complex, because it involves HLA matching, vascular anatomy, cytomegalovirus exposure status etc., but donor kidney function is an important consideration in terms of ensuring the best recipient outcomes (30,31).…”
Section: Importance Of Gfr Assessment For Donor Candidatesmentioning
confidence: 99%
“…Accurate estimation of the donor’s glomerular filtration rate (GFR) is crucial for not only ensuring the medical appropriateness of the donor but also for the prediction of future allograft performance. Researchers have pointed out higher GFR of the donors to be independently linked with better allograft outcomes [ 1 ]. Multiple approaches exist regarding the assessment of kidney functions while the majority of settings adopt 24-hour urinary creatinine clearance (urine-CrCl) or creatinine-based GFR estimations like “Modification of Diet in Renal Disease (MDRD)” or “Cockcroft-Gault (CG) equation” [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%